Perbandingan Variasi Lamanya Waktu Penyangraian Terhadap Kadar Kafein Pada Biji Kopi Robusta Secara Spektrofotometri UV-Vis - Panji Ratih Suci; Vania Angel; Nur Aini (Pusat Riset dan Inovasi Nasional, 2024)
Robutsta coffee is one of the most popular beverages in the world is consumed by many people. The main compound in coffee beans is caffeine. This compound affects the central nervous system, muscles, and kidneys. Caffeine cluster has kromoform, so it can be read using its absorbance of UV-Vis spectrophotometry. This research aims to know the level of caffeine in coffee beans with variation of roasting time duration. The determination of the levels of caffeine by using quantitative analysis, by way of determination of wavelength maximum, operating time, raw curve, and the determination of the levels of caffeine on the sample with variations of roasting time. Determination of the wavelength, the parent solution taken 10 ml, 50 ml measuring flask put in added HCI 0,1 N up to the mark with a boundary. The next assigment that is the determination of the levels of caffeine in samples. Each sample taken as many 3 ml filtrate into a 50 ml measuring flask, then added HCI 0,1 N up to the mark with a boundary. The result obtained in this research is the maximum wavelength obtained 274,0 nm. The sample content of raw robusta coffee beans is an average of 1,77% and robusta coffee bean content with variations of roasted time of 10 minutes is an average of 1,62 %, roasted time of 15 minutes is an average of 1,31 %, and roaster time of 21 minutes is an average of 1,10 %. The duration of the roasting test indicates that is a significant difference in caffeine content.